ANGPTL3 orchestrates hepatic fructose sensing and metabolism - Meng Zhao; Karen Y. Linde-Garelli; Zeyuan Zhang; David Toomer; Saranya C. Reghupaty; John Isaiah Jimenez; Laetitia Coassolo; Lianna W. Wat; Daniel Fernandez; Katrin J. Svensson (Cell Reports, 2025)
Summary: Fructose metabolism is linked to metabolic dysfunction-associated steatotic liver disease (MASLD), but the regulatory mechanisms governing fructose uptake remain poorly understood. Here, we demonstrate that MASLD livers exhibit increased uptake of fructose-derived carbons compared to healthy livers and identify that the MASLD hepatocyte secretome can increase fructose metabolism. By performing fractionation and untargeted proteomics, we uncover a role for Angiopoietin-like 3 (ANGPTL3) as a regulator of hepatic fructose metabolism, independent of its role as a lipoprotein lipase (LPL) inhibitor. Circulating ANGPTL3 levels increase in response to fructose exposure, consistent with an action as a fructose sensor. Angptl3 knockdown in the liver resulted in a significant reduction in the uptake of hepatic fructose metabolites in vivo and downregulation of the facilitative hepatic fructose transporter slc2a8 (GLUT8) and fructolysis enzymes. This work demonstrates the existence of extracellular control of hepatic fructose metabolism through ANGPTL3.